Effects of Drying Temperature on Carnation Flowers: A Study of Qualitative Aesthetic Attributes - , Shivkumar Mahadeo Wararkar; , SR Dalal; , Shiva Nand Mohan Mishra (Archives of Current Research International, 2025)
The investigation entitled Effects of Drying Temperature on Carnation Flowers: A study of qualitative aesthetic attributes was conducted in the Laboratory, Department of Horticulture, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola during the years 2015-16 and 2016-17. The experiment was laid out in Randomized Block Design with four replications and six treatments viz. 1, 1.5, 2, 2.5, 3 and 3.5 minutes. Cabinet oven drying for 3.5 minutes scored maximum scores for aesthetic acceptability, appearance, brittleness, colour, shape and texture. Maximum aesthetic acceptability scores 3.60, 3.63 and 3.61 were observed for 3.5 min. Flowers dried for 3.5 min scored maximum 3.50, 3.63 and 3.56 for appearance. Maximum color scores were 3.70, 3.63 and 3.66 for 3.5 min. Maximum brittleness scores 3.75, 3.70 and 3.73 were observed for 3.5 min. The flowers dried by hot air oven for the duration of 3.5 minutes scored maximum 3.68, 3.70 and 3.69 scores for shape. Maximum texture scores 3.73, 3.70 and 3.71 were observed for 3.5 min.